Research on Quantitative Calculation Method of Accident Scope of Gathering and Transportation Station - Lin Chen; Hang Tong; Zheng Liu; Zhi Zhang; Pengfei Mou (Energies, 2022)
In order to ensure the security and stability of oilfield gathering and transportation stations and to improve the risk assessment method, this paper proposes an evaluation method that can fully and quantitatively calculate the impact range of process equipment and pipelines in the event of fire and explosion accidents based on API 581-2016 Quantitative Risk Assessment Technology. It mainly analyzes and calculates the leakage type, leakage rate and total leakage amount, combined with the occurrence probability of various failure situations, the casualty area and the fact that equipment damage could be finally determined. In addition, PHAST Software is used to verify this method. The average deviation of the calculation results is very small, which shows that the method is completely feasible and accurate. In order to further correct the error, specific correction methods and formulas are also proposed. This theoretical calculation method greatly improves the quantitative evaluation method of oil field gathering and transportation stations, and lays a solid foundation for the quantitative calculation of failure consequences in the future.